Dual‐coupling networks engineering of self‐assembled ferromagnetic microspheres with enhanced interfacial polarization and magnetic interaction for microwave absorption - Chunyang Xu; Xuhui Xiong; Yiqian Du; Xiaowei Lv; Zhengchen Wu; Kaicheng Luo; Yuetong Qian; Renchao Che (InfoMat)
Abstract The simultaneous enhancement of magnetic and dielectric properties in nanomaterials is becoming increasingly important for achieving exceptional microwave absorption performance. However, the engineering strategies for modulating electromagnetic responses remain challenging, and the underlying magnetic‐dielectric loss mechanisms are not yet fully understood. In this study, we constructed novel dual‐coupling networks through the tightly packed Fe3O4@C spindles, which exhibit both dielectric and magnetic dissipation effects. During the spray‐drying process, vigorous self‐assembly facilitated the formation of hierarchical microspheres composed of nanoscale core‐shell ferromagnetic units. Numerous heterogeneous interfaces and abundant magnetic domains were produced in these microspheres. The integrated dielectric/magnetic coupling networks, formed by discontinuous carbon layers and closely arranged Fe3O4 spindles, contribute to strong absorption through intense interfacial polarization and magnetic interactions. The mechanisms behind both magnetic and dielectric losses are elucidated through Lorentz electron holography and micromagnetic simulations. Consequently, the hierarchical microspheres demonstrate excellent low‐frequency absorption performance, achieving an effective absorption bandwidth of 3.52 GHz, covering the entire C‐band from 4 to 8 GHz. This study reveals that dual‐coupling networks engineering is an effective strategy for synergistically enhancing electromagnetic responses and improving the absorption performance of magnetic nanomaterials.